Punishment of rape offender in Malaysia as under penal code: a review / Elly Zurina Mohamad...[et al.] - Mohamad, Elly Zurina; Mohd Maulud, Nurul Fadhilah; Sabri, Noor Syahirah; Tunku Hishammudin, Tunku Erika Nabila (2009)
The last two semesters had been dedicated to conduct a research based on the complaints made by many bodies and publics concerning rape cases. The research was done with the objective to find out what is the adequate punishment of rape to deter the offender and make a review on the punishment of rape offender in Malaysia after comparing with other country's punishment available in present. The relevancy of the application of the Penal Code and Criminal Procedure Code in finding out the sufficiency of the punishment of rape to the offenders were also been taken into consideration. We also want to investigate what is the role that should be played by the authorities and other bodies in order to reduce the number of rape cases. The cases that were being highlighted by the media is our main resources of information since most of these cases concerned on the punishment of rape that has been imposed to the offender before and after the amendment of the Penal Code and Criminal Procedure Code. We conducted interview session with experts that deal with the issue of rape in daily basis. The outcomes of these interviews were as expected. We benefited a lot from the interviews since most of the recommendations were relevant for the purpose of this research. Among questions forwarded to the respondents was on the sufficiency of the existing laws and whether there is a need for a more severe punishment of rape imposed in Malaysia. Our research was also based on the literatures written by authors specializing in this area and also materials we found online.